Identifying common confusing visual elements on packaging design of canned alcoholic beverages in Malaysia / Mohd Nasiruddin Abdul Aziz and Assoc. Prof. Dr Ghazali Daimin - Abdul Aziz, Mohd Nasiruddin; Daimin, Ghazali (Assoc. Prof. Dr ) (Universiti Teknologi MARA, 2016)
This research paper aims to define the confusing elements on alcoholic canned beverages and create a new visual sign to help the Muslim consumers in recognizing canned alcoholic beverages effectively. This research paper will examine the design elements on canned alcoholic packaging that may cause confusion to Muslim consumers. Based on a visual analysis of the said elements, a Haram logo was developed to enhance the contrasting designs between canned alcoholic and non-alcoholic beverages. The outcome of this research paper purposely will be transformed into a new and clearer visual sign for canned alcoholic beverages that are currently available to help Muslim consumers differentiating between the canned alcoholic and non-alcoholic beverages.